2014
DOI: 10.1371/journal.pone.0108369
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Newly Notified Pulmonary Tuberculosis Cases from 2004 to 2013 in Wuhan, China

Abstract: BackgroundAlthough there was a report about the seasonal variation in Wuhan city, it only analyzed the prevalence data of pulmonary tuberculosis (TB) cases, and just studied the seasonality by subgroup of smear positive and negative from 2006 to 2010 by spectral analysis. In this study, we investigated the seasonality of the total newly notified pulmonary TB cases by subgroups such as time period, sex, age, occupation, district, and sputum smear result from 2004 to 2013 in Wuhan by a popular seasonal adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 34 publications
4
31
0
Order By: Relevance
“…A similar study shows that the summer peak was mainly as a result of enhanced winter transmission of TB due to indoor crowding [21]. Another study in United States suggests that reduced winter exposure may not be a strong contributor to TB risk [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study shows that the summer peak was mainly as a result of enhanced winter transmission of TB due to indoor crowding [21]. Another study in United States suggests that reduced winter exposure may not be a strong contributor to TB risk [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variation is a considerable factor in regard to PTB, but the specific effects it has on the epidemic is not entirely clear since several studies have identified incidence peaks in winter, spring, and summer [911]. Furthermore, the interpretation of seasonality in relation to PTB risk is complicated due to the large number of factors to consider such as environmental factors (temperature, humidity, sunlight), social factors (crowding and person-to-person contact), and delays in the diagnosis and treatment of tuberculosis particularly in winter [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in various countries in the northern hemisphere have identi ed peak months of TB noti cation in spring (March to May) (4-10), late spring and early summer (April to June) (7,11,12), or summer (June to August) (13)(14)(15)(16). Trough months have been noted in the fall (September to November) (5), late fall and early winter (October to December) (4,6,11,12), or winter (January to February) (15).…”
Section: Introductionmentioning
confidence: 99%